Author Correction: Sequential formation and resolution of multiple rosettes drive embryo remodelling after implantation. Issue 12 (December 2018) - Christodoulou, Neophytos; Kyprianou, Christos; Weberling, Antonia; Wang, Ran; Cui, Guizhong; Peng, Guangdun; Jing, Naihe; Zernicka-Goetz, Magdalena
In the version of this Article originally published, the first name of author Guangdun Peng was spelled incorrectly as Guangdum. This has now been amended in all versions of the Article.